Temperature and scarification effects on the germination of Syagrus picrophylla seeds, a Brazilian native palm - Pivetta, K. F.L. [UNESP]; Takane, R. J.; Batista, G. S. [UNESP]; Romani, G. N. [UNESP]; Mazzini, R. B. [UNESP] (International Society for Horticultural Science (ISHS), 2012)
Syagrus picrophylla belongs to the Arecaceae family. Its propagation is made by seeds; however there is a lack of information in the literature about its seed germination. The objective of this work was to evaluate the effects of temperature and scarification on the germination of S. picrophylla seeds. The experiment was carried out at the State University of São Paulo, Jaboticabal Campus, Brazil. The experimental design was entirely randomized in a factorial arrangement 5 × 2 (five temperature conditions combined with or without mechanical scarification. The number of germinated seeds that showed primary root protrusion was noted daily, and when the germination was stabilized, the germination (%G) and germination rate (GR) were calculated. The analysis of variance (ANOVA) was carried out for means comparing by the Tukey test at 5% confidence level. It was concluded that the greatest %G were obtained at 20-30°C (62%) and 25-35°C (59%) alternated temperatures; %G and GR were similar for both scarified and non-scarified seeds, and there was a faster germination at 20-30°C alternated temperature.
Keywords: Arecaceae; Embryo dormancy; Germination rate; Seeds; Sexual propagation